The Impact of Electronic Information Systems on Personal and Social Identity: Towards a Theoretical Framework for Evaluation and Research in the Kurdistan Region - Hosseini, Dr. Sayyid Mahdi (Sulaimani Journal for Humanities, 2025)
Social identity, at both the individual and collective levels, is formed and evolves over time through social behaviors and activities, experiences, and according to cultural contexts and self-assessments. Any real or virtual environment that provides individuals with opportunities to connect, interact, participate in activities, and allows for the formation of groups can be a space for the expression and exchange of identities. In today's world of the internet, which is now accessible to all individuals and communities, it has an impact on national identity. Unfortunately, this has not been done in a serious way, and the theoretical principles have not been introduced to Kurdish readers. To begin exploring this scientific field, this article attempts to present the theories that have been published on the relationship between national identity and electronic systems. It also provides a foundation for scientific research on the effects of electronic information systems on Kurdish identity. This study was conducted as a qualitative and textual analysis of scientific sources. For this purpose, after selecting the terms and searching for articles and books, the search results were categorized based on the summaries of the articles and the introductions of the books. An important criterion was the use of a theoretical framework and an analysis of the relationship between national identity and electronic systems, as well as a description of cultural organizations. The results of the evaluation and selection were divided into four articles and two books, which are described in the Achievements section. As a result of this study, it was found that regarding the relationship between identity and electronic information systems and the role of cultural centers, the sources have proposed theoretical and conceptual foundations for research in the following areas: 1) the nature of identity, 2) the role of personal behavior, 3) the digital environment, 4) political influence, and 5) the role of cultural organizations. The relationship between these elements was also proposed as a comprehensive model, and, based on the analysis table, key concepts for consideration in the study were identified. Finally, based on the status of electronic information system use in the Kurdistan Region, a number of recommendations were made.
Keywords: National Identity; Theoretical Principles; Electronic Information System; Kurdistan Region; Resource Analysis